Broadband heterogeneous terahertz frequency quantum cascade laser. Issue 21 (1st October 2018) - Li, L.H.; Garrasi, K.; Kundu, I.; Han, Y.J.; Salih, M.; Vitiello, M.S.; Davies, A.G.; Linfield, E.H.
Abstract : The authors demonstrate a broadband, heterogeneous terahertz frequency quantum cascade laser by exploiting an active region design based on longitudinal optical‐phonon‐assisted interminiband transitions. They obtain continuous wave laser emission with a threshold current density of ∼120 A/cm 2, a dynamic range of ∼3.1, and an emission spectrum spanning from 2.4 to 3.4 THz at 15 K.